Comparative study of metabolic profile of women presenting with polycystic ovary syndrome in relation to body mass index - S., Akshaya; Bhattacharya, Ratnaboli (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, ovulatory dysfunction and polycystic ovaries (PCO). The objective was to study and compare the metabolic effects of PCOS in lean PCOS (BMI <23) and obese PCOS (BMI >23). Methods: Fifty healthy women who were euthyroid with age range 15-38 years who presented to gynecology OPD and diagnosed to have PCOS according to ESHRE/ASRM criteria were included in the study. BMI (body mass index) was calculated by the formula weight in kg/height in meter square. BMI were calculated were divided into 2 groups. Lean PCOS found in patients with BMI <23 kg/m2 and overweight/obese PCOS found in patients with BMI >23 kg/m2. Results: Hypertension, deranged lipid profile, insulin resistances were frequently seen in obese PCOS than in lean PCOS. Deranged GTT (glucose tolerance test) was not statistically significant in these two groups p=0.15. Conclusions: The study concludes that obese PCOS were at higher risk of developing hypertension, deranged lipid profile and insulin resistance than lean PCOS as obesity is significant contributor to metabolic syndrome. Glucose intolerance was present in both obese and lean PCOS.